2007
DOI: 10.1109/tvlsi.2007.893578
|View full text |Cite
|
Sign up to set email alerts
|

Interconnect Lifetime Prediction for Reliability-Aware Systems

Abstract: Abstract-Thermal effects are becoming a limiting factor in high-performance circuit design due to the strong temperature dependence of leakage power, circuit performance, IC package cost, and reliability. While many interconnect reliability models assume a constant temperature, this paper analyzes the effects of temporal and spatial thermal gradients on interconnect lifetime in terms of electromigration, and presents a physics-based dynamic reliability model which returns reliability equivalent temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Overall, the EM phenomenon for high current densities can result to the metal failure, irrespective of the metal in question [125][126][127]. Therefore, the EM can be compensated by using a laminating barrier such as tungsten (W) and titanium(Ti).…”
Section: Electro-migration (Em)mentioning
confidence: 99%
“…Overall, the EM phenomenon for high current densities can result to the metal failure, irrespective of the metal in question [125][126][127]. Therefore, the EM can be compensated by using a laminating barrier such as tungsten (W) and titanium(Ti).…”
Section: Electro-migration (Em)mentioning
confidence: 99%
“…This is increasingly because of thermally-induced accelerated failure rates. For example, one analysis of electromigration-related failure of VLSI interconnect suggests that the mean time to failure is inversely related to the operating temperature [8]:…”
Section: Implications For Reliabilitymentioning
confidence: 99%
“…The most representative ones include time-dependent dielectric breakdown (TDDB) in the gate oxides, electromigration (EM) and stress migration (SM) in the interconnects, and negative bias temperature instability (NBTI) stresses that shift PMOS transistor threshold voltages. Many widely accepted reliability models for the above failure mechanisms at device and circuit level have been proposed and empirically validated by academia and industry [19], [20], [21], [22], [23], [24], and it is shown that they are strongly related to the temperature and voltage applied to the circuit.…”
Section: Ic Lifetime Reliabilitymentioning
confidence: 99%